Metode Resitasi dalam Pembelajaran Al-Qur’an Hadist Siswa Kelas VIII di Madrasah Tsanawiyah Hidayatul Mubtadiin Sidoharjo Kecamatan Jati Agung Lampung Selatan - Ria Asnani; Sarpendi Sarpendi; Mustafida Mustafida (Journal on Education, 2024)
This research aims to examine the effectiveness of the recitation method in learning Al-Qur'an Hadith for class VIII students at Madrasah Tsanawiyah. The recitation method, which involves repeating and reciting verses from the Koran and hadith over and over again, is expected to improve students' understanding, memorization and reading ability of religious texts. This research uses a qualitative approach with a case study method. Data was obtained through observation, in-depth interviews with teachers and students, as well as analysis of learning documents. The results of the research show that the application of the Recitation Method in Learning Al-Qur'an Hadith for Class VIII B Students at Madrasah Tsanawiyah Hidayatul Mubtadiin has been carried out according to the steps for applying the recitation method, starting from the Presenting material phase, the question and answer process phase, the Assignment phase, the Guiding work results, and the phase of assessing work results. The types of recitation methods can be individual assignments or group assignments (according to the directions given by the teacher). The supporting factors for the recitation method in learning Al-Qur'an Hadith are: Internal factors where the students themselves can read the Al-Qur'an, although not all of it, but in terms of reading it is sufficient even though it still needs improvement both in terms of reading and in terms of recitation. as well as external factors, there are sufficient and adequate facilities to be used in implementing this recitation method, such as the Al-Qur'an, worksheet books and literature books which are ready for MTs Hidayatul Mubtadiin students to use in the practice of reading the Al-Qur'an and also as a place to study the Al-Quran. 'an.